Occupational and Environmental Ultraviolet–Sunlight Exposure, Including Outdoor Agricultural Work, and the Risk of Cataract: A Systematic Review and Meta-Analysis of Observational Studies - Kadek Diah Pramesti Ken Wardana; Sari Marina; Putu Daivi Prakriti (HM Publisher, 2026)
Background.Cataract remains the leading cause of avoidable blindness worldwide, and occupational sunlight exposure is suspected as a modifiable risk factor among outdoor workers, including agricultural workers in tropical low- and middle-income countries (LMICs) such as Indonesia. Previous quantitative syntheses pooled mixed exposure-contrast metrics into a single estimate and obtained heterogeneity in excess of I2 = 95%, providing limited interpretable guidance for clinicians and policy makers. Methods.A systematic search of PubMed/MEDLINE was conducted and supplemented by citation tracing and translated search strings for Scopus, Embase, Web of Science and Cochrane CENTRAL. Eligible studies were observational analyses of adults reporting an OR, HR or relative risk with a 95% CI for occupational or environmental UV-sunlight exposure and cataract. Risk of bias was assessed using the Newcastle-Ottawa Scale. Effect estimates were pooled using DerSimonian-Laird random-effects models with REML and Hartung-Knapp-Sidik-Jonkman sensitivity estimators. Results.Seven observational studies (combined n approximately 60,000) met the inclusion criteria. Pooled OR from four extreme high-vs-low contrast studies: 6.52 (95% CI 4.12-10.33; I2 = 67%). Three modest per-unit/ever-vs-never studies pooled at OR/HR 1.09 (95% CI 1.04-1.14; I2 = 0%). The contrast-type moderator explained approximately 45% of between-study heterogeneity (p < 0.001). Conclusion.Occupational and environmental UV-sunlight exposure is associated with a clinically significant increase in cataract risk. The magnitude depended on the exposure contrast. The findings support targeted ocular-protection programmes for outdoor agricultural workers in high-insolation LMICs such as Indonesia.